1993
DOI: 10.1108/03090569310024530
|View full text |Cite
|
Sign up to set email alerts
|

The Market for Luxury Goods: Income versus Culture

Abstract: Points out that identifying appropriate market segmentation bases has been a recurrent problem in marketing. Compares the predictive power of income and attitude towards cultural change in the context of luxury goods. The results show that those two indicators are rather independent from each other and contribute almost equally to explaining luxury goods consumption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
288
2
17

Year Published

1998
1998
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 467 publications
(316 citation statements)
references
References 0 publications
9
288
2
17
Order By: Relevance
“…These people may be characterized by overconsumption, as their class consciousness, if strongly shaped by lifestyle, is higher than their objective, economic class. The prominence of overconsuming people with seemingly mistaken class consciousness might be inevitable in status-competitive, consumer societies to the extent that one's cultural consumption is not strongly restricted by budgets at hand but significantly affected by striving to be ''on trend'' (Dubois & Duquesne, 1993). We also confirmed that major findings under the assumption of the infinite range of assimilation also hold true for finite ranges of assimilation which are considerably larger than those of distinction.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…These people may be characterized by overconsumption, as their class consciousness, if strongly shaped by lifestyle, is higher than their objective, economic class. The prominence of overconsuming people with seemingly mistaken class consciousness might be inevitable in status-competitive, consumer societies to the extent that one's cultural consumption is not strongly restricted by budgets at hand but significantly affected by striving to be ''on trend'' (Dubois & Duquesne, 1993). We also confirmed that major findings under the assumption of the infinite range of assimilation also hold true for finite ranges of assimilation which are considerably larger than those of distinction.…”
Section: Discussionsupporting
confidence: 77%
“…Note that cultural consumption in the contemporary society is significantly influenced by ''social status'' (Alderson et al, 2007) and cultural values (Dubois & Duquesne, 1993). Consumer research and economic psychology report that popularized luxury consumption is influenced by social aspirations (Karlsson, Dellgran, Klingander, & Gärling, 2004) and psychological indulgence (e.g., Kivetz & Simonson, 2002).…”
Section: Theory and Model Of Assimilation-distinctionmentioning
confidence: 99%
“…The economic value of luxury, fashion and status products is argued to be substantial. 31 Mason 32 argued that people express themselves through consumption in a myriad of ways, and in this context, products and brands have the ability to communicate messages to others, in that product styles determine how consumers Materialism as a word or trait is generally viewed in a very negative sense and is clearly reflected in the various denouncements of materialism by all major world religions and in numerous other critiques. It is interesting to note from the previous research that it has been established that materialism is viewed as an evil phenomenon and that the USA is commonly viewed as a country that encourages and breeds this evil phenomenon.…”
Section: Fashion Marketingmentioning
confidence: 99%
“…Although it could be assumed that a primary indicator for the purchase of high-price goods would be the income or the economic power of consumers, it was shown that their cultural background has approximately the same predictive power to explain the purchase of luxury goods (Dubois & Duquesne, 1993). Socio-economic and cultural background however does not only play a role in consumption of luxury goods but in shopping behaviour in general (Arnould & Thompson, 2005;McCracken, 1986).…”
Section: Cultural Ergonomicsmentioning
confidence: 99%